Etika Kebebasan Berekspresi di Media Sosial dalam Perspektif Kristen - Yosua, Asep; Hermanto, Yanto Paulus (Sekolah Tinggi Teologi Berita Hidup, 2025)
Abstract This study investigates the boundaries of freedom of expression on social media from a Christian faith perspective, considering its potential impact on relational dynamics within the Body of Christ, including the emergence of hate speech, the spread of inaccurate information, and the potential for division. This research is relevant given the need to strengthen faith-based literacy among digital generations so they can communicate ethically in digital spaces, recognizing the strategic role of the church, schools, and families in this character-forming process. The research aims to formulate Bible-based ethical principles for expression on social media, particularly drawn from James 3, Ephesians 4:29, and 1 Corinthians 6:12. The method used is qualitative library research, analyzing biblical texts and theological literature through descriptive-analytical and thematic synthesis approaches. The novelty of this study lies in formulating four concrete ethical-theological boundaries for expression in the digital world: Truth (fact-based), Love (respecting the dignity of others), Responsibility (every interaction carries moral consequences), and Purpose (glorifying God and building up fellowship). These findings are expected to serve as a guide for Christians to use social media responsibly, so that digital space can become a constructive medium for faith witness and fellowship strengthening. Abstrak Penelitian ini menyelidiki batas-batas kebebasan berekspresi di media sosial menurut iman Kristen, dengan mempertimbangkan potensi dampaknya terhadap dinamika relasi dalam Tubuh Kristus, termasuk kemunculan ujaran kebencian, penyebaran informasi tidak akurat, dan potensi perpecahan. Penelitian ini relevan dilakukan mengingat perlunya penguatan literasi iman bagi generasi digital agar mampu berkomunikasi secara etis di ruang digital, mengingat peran strategis gereja, sekolah, dan keluarga dalam proses pembentukan karakter tersebut. Tujuan penelitian adalah merumuskan prinsip-prinsip etis berbasis Alkitab untuk berekspresi di media sosial, khususnya berdasarkan Yakobus 3, Efesus 4:29, dan 1 Korintus 6:12. Metode yang digunakan adalah penelitian pustaka kualitatif dengan menganalisis teks Alkitab dan literatur teologi melalui pendekatan deskriptif-analitis dan sintesis tematik. Kebaruan hasil penelitian adalah perumusan empat batas etis-teologis konkret untuk berekspresi di dunia digital: Kebenaran (berbasis fakta), Kasih (menghargai martabat sesama), Tanggung Jawab (setiap interaksi memiliki konsekuensi moral), dan Tujuan (memuliakan Tuhan dan membangun persekutuan). Temuan ini diharapkan dapat menjadi panduan bagi orang Kristen dalam memanfaatkan media sosial secara bertanggung jawab, sehingga ruang digital dapat menjadi medium yang konstruktif bagi kesaksian iman dan penguatan persekutuan.